Pain modulation by intranasal oxytocin and emotional picture viewing — a randomized double-blind fMRI study - Zunhammer, Matthias (Sci Rep, 2016)
The hormone oxytocin has been hypothesized to influence the emotional dimension of pain. This randomized, placebo-controlled, double-blind, crossover study explored whether intranasal oxytocin and emotional context can affect heat pain perception in 30 healthy male volunteers. After receiving 36 IU oxytocin or placebo, participants underwent functional Magnetic Resonance Imaging (fMRI) during which noxious and non-noxious thermode heat stimuli were applied. Simultaneously, scenes from the International Affective Pictures System (IAPS) with positive, neutral, and negative emotional valence were shown. Heat intensity and unpleasantness ratings were obtained. The activity of whole-brain correlates of heat processing was quantified via multi-voxel pattern analysis. We observed no appreciable main effects of oxytocin on ratings or neural pain correlates. Effects of emotional picture valence on ratings were smaller than reported in previous studies. Nevertheless, oxytocin was found to significantly enhance the influence of picture valence on unpleasantness ratings at noxious heat levels. No corresponding changes in whole-brain correlates of heat intensity processing were found. Our study provides evidence that intranasal oxytocin increases the effects of emotional context on the subjective unpleasantness of experimental heat pain. Future studies are needed to determine whether this effect can be utilized in clinical settings.